Economic development dimension of intellectual property as investment in international investment law - Ivan Stepanov (The Journal of World Intellectual Property, 2020)
Intellectual property (IP) and foreign direct investment (FDI) are seen as important contributors to economic development. However, once given a closer look, a complex economic landscape emerges. Although, both IP and FDI can be beneficial to the economic development of a country their presence does not automatically guarantee it. From a legal perspective, the treaties governing the two international legal regimes, international IP law and international investment law (IIL), reflect the positive developmental aspirations ascribed to IP and FDI. Nevertheless, once these international treaties are put to the test in international adjudication, economic development becomes a contested notion. In particular, investor-state dispute settlement (ISDS) tribunals are often confronted with economic development as a legal concept and the way they treat it can vastly differ. By relying on the Salini test in ISDS cases dealing with IP, the Tribunals had the chance to address the developmental dimension of IP as FDI. Philip Morris v. Uruguay and Bridgestone v. Panama give a detailed outlook on the different outcomes such considerations might result in. Focusing on those cases this article will argue that economic development deserves a place in the realm of IP and IIL.
Keywords: 340; economic development; foreign direct investment; ISDS; key topics; organizations and agreements; TRIPS